Educational Research: An Ethical Commitment to the Promotion of the Quality of Life and the Respect for Human Dignity - Horacio Ademar Ferreyra; Georgia Blanas de Marengo (Universidad Autónoma de Madrid, 2016)
Currently, management of information and scientific knowledge is key. The development of research and application of results in all spheres of human activity is the basis of the "information economy" and "knowledge societies ". Several authors argue that the low capacity to produce, disseminate and use knowledge to guide and sustain the processes of economic and social development seems to be a common deficit of States and societies in Latin America. We are convinced that the research provides an indispensable basis for the improvement of education policies and processes and the functioning of institutions, training programs and processes in context. We believe that one of the commitments and ethical challenges of educational research is to investigate and define the scope of what constitutes quality education to reflect on what are the perspectives, dimensions, indicators, mechanisms and instruments for checking, verification, confrontation, evaluation and accreditation. We understand that the term educational quality is far from being a univocal concept of scope and much less standardized, on the contrary we believe that it must be built on a consensus process involving the University with the agencies responsible for assessing the quality of education. In the wake of the adoption of immediate and technocratic concepts devoid of cultural content and political science and contemporary education, comes a renewed concern in academic and political circles about the need to adopt a concept of substantive quality of human life, mainstreaming in the scientific and educational currently.